2019
DOI: 10.1253/circrep.cr-19-0020
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Mobile Cloud Electrocardiography System on Door-to-Balloon Time in Patients With Acute Coronary Syndrome in Oita Prefecture

Abstract: Background: The mobile cloud electrocardiography (C-ECG) system is useful for reducing door-to-balloon (DTB) time in patients with acute coronary syndrome (ACS), but few studies have reported the usefulness of the C-ECG system across a wide provincial prefecture, such as Oita, in Japan. Methods and Results: On 17 April 2017, the C-ECG system was integrated into the Oita remote image transmission system, in 10 ambulances of 10 respective fire departments in Oita Prefectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…However, we reported FMCTB time was 80 (63-92) min in this study, even in the Conventional group. Similarly, door-to-balloon time and door-to-catheter laboratory time of prehospital-ECG group in the previous study were 68 (52-83) min and 27 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) min. However, those of the Conventional group in this study were 59 (38-67) min and 24 (15-41) min, espectively.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, we reported FMCTB time was 80 (63-92) min in this study, even in the Conventional group. Similarly, door-to-balloon time and door-to-catheter laboratory time of prehospital-ECG group in the previous study were 68 (52-83) min and 27 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) min. However, those of the Conventional group in this study were 59 (38-67) min and 24 (15-41) min, espectively.…”
Section: Discussionmentioning
confidence: 64%
“…SCUNA is a MC-ECG transmission system [11][12][13]. SCUNA was shown to be effective for reducing door-to-balloon time in patients with acute coronary syndrome [28]. Previous studies, such as Kawakami et al, had reported in 2016 [29] that FMCTB time was 97 (82-112) min in the group with the use of prehospital electrocardiogram.…”
Section: Discussionmentioning
confidence: 99%
“…The authors ascribed the results to a prehospital 12-lead ECG being performed reported that usage of C-ECG across a wide area of Oita, Japan, significantly reduced DTBT by 26 min and door-tocatheterization laboratory time by 20 min. 6 It is important to reduce the time from onset to reperfusion for a better outcome for patients with STEMI. The goal of treatment in STEMI is to achieve reperfusion within 120 min from onset, which means initiating therapy within 30 min from first contact with medical personnel for fibrinolysis in emergency department at hospital and catheter treatment to within 90 min from the first contact with medical personnel for PCI.…”
Section: Discussionmentioning
confidence: 99%
“…5 We used a mobile cloud electrocardiography system (C-ECG) as the prehospital 12-lead ECG and measured its effect on door-to-balloon times in Oita Prefecture. 6 Transmitting the prehospital 12-lead ECG by emergency teams to the hospital improve outcomes by enabling preparation of the cardiac catheterization room before patient arrival, early convening of the transmission system. The ECG in the cloud server can be accessed simultaneously from personal computers, smartphones, and tablets anywhere after access key authentication.…”
Section: Prehospital Ecg System In Oitamentioning
confidence: 99%
“…Today, the market offers single-channel or multi-channel Holters, with many complementary sensors, with or without a hospital certificate. Their price varies from tens of euros [42] to several thousands (EC-12H 12-Channel Holter ECG system by LabTech, Hungary or CardioMera ECG Holter Monitor, Medusoft, Australia) [43][44][45][46][47] depending on the quality and properties offered.…”
Section: Electrocardiography and Respirationmentioning
confidence: 99%